UPAYA MENINGKATKAN MINAT NASABAH PADA PRODUK IB HIJRAH WADIAH DI BANK MUAMALAT INDONESIA (BMI) KANTOR CABANG PEMBANTU (KCP) MADIUN - Prastika, Rima (Fakultas Ekonomi Bisnis Islam, 2025)
The development of banks today has undergone many changes, every bank is faced with problems regarding marketing, therefore the bank must be able to formulate the right marketing strategy, the bank needs to know its competitors. The Bank must continue to compare its products, prices, and promotions with those of its competitors, in this way the Bank will be able to find existing shortcomings or advantages. The purpose of this research is to find out to find out what strategies the bank has done to increase interest in becoming a customer of Hajj iB Savings Products at Bank Muamalat Indonesi KCP Madiun. And the second is to find out the implications of IB Hijrah Wadiah savings products at Bank Muamalat Indonesia (BMI) Madiun Sub-Branch Office (KCP) on customer interest. This research includes field research (Field research), while the nature of this research is descriptive qualitative This research uses interview data collection techniques and documentation Interviews were conducted with Bank Muamalat Indonesia KCP Madiun and Bank Muamlat Indonesia KCP Madiun customers. Then for the data source used by researchers is to check the data validity technique. The results showed that 1) The strategy to increase interest in becoming a customer of iB Hijrah Wadiah Savings Products is by socializing and making comparisons with other banks. That way the bank will know the advantages and disadvantages so that it can be input and improve what needs to be improved. 2) Factors that influence public interest in Hajj iB hijrah savings products at Bank Muamalat Indonesia KCP Madiun are internal factors and external factors. The factors that most influence customer interest are cultural factors in terms of religion, social factors in terms of reference groups, family, and social roles, personal factors in terms of age and economic conditions, psychological factors of motivation and services provided by Bank Muamalat KCP Madiun. The internal constraints found at BMI KCP Madiun are limited branch offices and lack of human